Advancing therapeutic frontiers: a pipeline of novel drugs for luminal and perianal Crohn's disease management - Luisa Bertin; Martina Crepaldi; Miriana Zanconato; Greta Lorenzon; Daria Maniero; Caterina de Barba; Erica Bonazzi; Sonia Facchin; Marco Scarpa; Cesare Ruffolo; Imerio Angriman; Andrea Buda; et al. (Therapeutic Advances in Gastroenterology)
Crohn’s disease (CD) is a chronic, complex inflammatory disorder of the gastrointestinal tract that presents significant therapeutic challenges. Despite the availability of a wide range of treatments, many patients experience primary non-response, secondary loss of response, or adverse events, limiting the overall effectiveness of current therapies. Clinical trials often report response rates below 60%, partly due to stringent inclusion criteria. Emerging therapies that target novel pathways offer promise in overcoming these limitations. This review explores the latest investigational drugs in phases I, II, and III clinical trials for treating both luminal and perianal CD. We highlight promising therapies that target known mechanisms, including selective Janus kinase inhibitors, anti-adhesion molecules, tumor necrosis factor inhibitors, and IL-23 selective inhibitors. In addition, we delve into novel therapeutic strategies such as sphingosine-1-phosphate receptor modulators, miR-124 upregulators, anti-fractalkine (CX3CL1), anti-TL1A, peroxisome proliferator-activated receptor gamma agonists, TGFBRI/ALK5 inhibitors, anti-CCR9 agents, and other innovative small molecules, as well as combination therapies. These emerging approaches, by addressing new pathways and mechanisms of action, have the potential to surpass the limitations of existing treatments and significantly improve CD management. However, the path to developing new therapies for inflammatory bowel disease (IBD) is fraught with challenges, including complex trial designs, ethical concerns regarding placebo use, recruitment difficulties, and escalating costs. The landscape of IBD clinical trials is shifting toward greater inclusivity, improved patient diversity, and innovative trial designs, such as adaptive and Bayesian approaches, to address these challenges. By overcoming these obstacles, the drug development pipeline can advance more effective, accessible, and timely treatments for CD.